Poncirus trifoliata vs. Citrus junos rootstocks: reshaping lemon rhizosphere microecology through microbial and metabolic reprogramming - Long, Chunrui; Fu, Xiaomeng; Wu, Qingjiang; Wang, Shaohua; Zhou, Xianyan; Mao, Jiamei; Guo, Lina; Shi, Wenbin; Yang, Hongxia; Yang, Tiankun; Du, Yuxia; Yue, Jianqiang; et al. (Frontiers in Microbiology, 2025)
IntroductionTrifoliate orange (Poncirus trifoliataL. Raf) and “Ziyang Xiangcheng” (Citrus junos Sieb. ex Tanaka) are the predominant rootstocks for lemon production in China, exhibiting distinct adaptations to soil pH and differential impacts on plant resilience. As pivotal mediators of scion-soil interactions, rootstocks have emerged as key research targets for their regulatory potential in rhizosphere microbial communities and metabolites.MethodsPot-cultured systems were established with lemon (Citrus × limon “Eureka”) saplings grafted onto trifoliate orange (PTL) and “Ziyang Xiangcheng” (CJL) rootstocks. Integrated metagenomic and GC-MS metabolomic approaches were employed to analyze rhizosphere microbial communities and metabolites.ResultsThe results demonstrated no significant difference in rhizospheric microbial α-diversity (richness) between PTL and CJL, although PTL exhibited higher evenness. β-Diversity and LEfSe analysis revealed significant structural divergence in communities. A total of 15 differentially enriched genera across three phyla were identified, among which Pseudomonas, Cupriavidus, and Burkholderia in CJL, along with Sphingobium in PTL, exhibited strong effects. Random forest modeling identified 15 key differential metabolites, with 4 significantly upregulated in CJL and 11 in PTL. Microbial-metabolite correlation and GSEA analysis uncovered 10 core pathways involving genetic information processing, energy metabolism, environmental adaptation, and disease resistance mechanisms. Soil analysis showed CJL significantly surpassed PTL in organic matter content, catalase activity and plant height, whereas PTL exhibited superior cellulase, sucrase and urease activities. Mechanistically, PTL appears to recruit Pseudomonas mediterranea via 1-Monostearin secretion to activate glycerolipid metabolism, enhancing drought tolerance. Its caffeate and salicyl alcohol-β-glucoside secretions potentially mobilize Sphingobium and Ensifer adhaerens to regulate amino sugar metabolism, promoting carbon sequestration and root defense. Conversely, CJL likely employs L-alanine exudation to recruit Pseudomonas putida, triggering exopolysaccharide biosynthesis through arginine-proline metabolism as a key tolerance mechanism (such as drought tolerance and alkali tolerance)DiscussionThe findings elucidate rootstock-specific modulation of rhizosphere microecosystems, highlighting distinct microbial-metabolite interactions and tolerance mechanisms. These results provide theoretical support for precision rootstock selection and microbiome engineering to advance sustainable citrus production.